Assessment of the contribution of hazardous air pollutants from nigeria's petroleum refineries to ambient air quality. Part 1. Issue 1 (1st January 2021) - Fakinle, Bamidele Sunday; Olalekan, Abiodun Paul; Odekanle, Ebenezer Leke; Bakut, Chinchong Blessing; Ogundokun, Roseline Oluwaseun; Sonibare, Jacob Ademola; Aremu, Charity O.
Abstract: This study investigated the contribution of anthropogenic emission of benzene from petroleum refineries to the Nigerian's ambient air quality with the view of understanding the impact of petroleum production facilities on host airshed. The Activities of the four existing and 22 proposed petroleum refineries in Nigeria were obtained from the Department of Petroleum Resources and these were combined with emission factors of different units at the refineries to estimate benzene emissions. No-control-measure option (worst case scenario) was assumed because of lack of information on control efficiency of the refineries. The study revealed that two of the existing refineries in one of the oil-producing cities in Nigeria released a total of 10.01 × 10 11 tons/year of benzene into the ambient air of the city, apart from additional 2.35 × 10 13 tons/year anticipated to be released from three of the proposed refineries into the ambient air of the same host community. If operated at full capacity, the estimated benzene emission from the four existing refineries stood at 5.50 × 10 13 tons/year while the 22 proposed refineries have the capacity of releasing additional 16.73 × 10 13 ton/year. On the overall, the contribution of benzene from refineries on yearly basis to Nigerian airshed was estimated to be 22.24 × 10 13 tons. These concentrations if not checked could lead to devastating environmental issues. Some mitigating measures were suggested to control and subsequently abate benzene emission from these refineries.